Low-melting-point glass for sealing ceramic and metal

By using low-melting point glass composed of silicon oxide, boron oxide and phosphorus oxide, the problem of mismatch in thermal expansion coefficients in ceramic and metal sealing is solved, and efficient and stable ceramic and metal sealing is achieved, which is suitable for a variety of high-temperature application scenarios.

CN119797769AInactive Publication Date: 2025-04-11EAST CHINA UNIV OF SCI & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510074709.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing ceramic and metal sealing materials and technologies are difficult to match the thermal expansion coefficient of ceramic and metal in high temperature environments, resulting in large stresses in the sealing area and easy cracking of the connection. The activated Mo-Mn method and the activated metal brazing method are complex and costly, so it cannot be suitable for low melting point metals and high temperature-resistant functional devices.

Method used

Low-melting point glass composed of three glass networks: silicon oxide, boron oxide and phosphorus oxide, is used to adjust the chemical composition and thermal expansion coefficient of the glass to achieve efficient sealing between ceramics and metals. This low-melting point glass has the characteristics of lead-free environmental protection, good sealing, high mechanical strength and good chemical stability, and is suitable for high-temperature sealing of 600~1000℃.

Benefits of technology

It realizes efficient sealing between ceramics and metals, reduces internal stress of sealing, improves mechanical strength and chemical stability of sealing, is suitable for sealing of a variety of ceramics and metal materials, and shows good acid corrosion resistance in high-temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses low-melting-point glass used for sealing ceramic and metal at the temperature of 600-1000 DEG C. The low-melting-point glass comprises a glass substrate, the low-melting-point glass is characterized in that the low-melting-point glass contains three glass network forming bodies of silicon oxide, boron oxide and phosphorus oxide, has relatively good affinity to ceramics and metal materials, has a relatively large regulation and control freedom degree of a thermal expansion coefficient, and has the characteristics of high sealing strength, good air tightness, strong chemical stability, good insulativity, no lead, environmental friendliness and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of sealing materials, and in particular to a low-melting-point glass composed of three glass network formers, namely silicon oxide, boron oxide and phosphorus oxide, which can be used for sealing ceramics and metals in the fields of fuel cell stacks, electronic components, integrated circuits, etc. Background Art

[0002] The sealing of ceramics and metals has important uses in the fields of integrated circuits, communication instruments, lighting displays, transportation equipment, aerospace equipment, etc. However, there are significant differences between ceramics and metals in terms of physical and chemical properties and material mechanics. In most cases, ceramics have a smaller thermal expansion coefficient, lower thermal conductivity, and poor thermal shock resistance than metals, and the surface of ceramics is difficult to be wetted by molten metal. Therefore, compared with metal-to-metal sealing or ceramic-to-ceramic sealing, ceramic-to-metal sealing is more difficult. Especially in some special application scenarios, it is still difficult to obtain a more ideal sealing effect using current sealing materials and technologies. For example, when the difference in thermal expansion coefficient between ceramics and metals is large, after high-temperature treatment, the sealing area often has a large residual internal stress, resulting in cracking of the connection. This requires that the sealing material not only has high mechanical strength and matching thermal expansion coefficient, but also has good affinity and adhesion to both ceramic and metal materials.

[0003] In 1935, Siemens of Germany invented the metal powder sintering method for sealing ceramics and metals in vacuum electron tubes. On this basis, researchers have developed ceramic metallization processes such as activated Mo-Mn method, direct copper coating method, active metal brazing method, and ion sputtering method in the following decades. Among them, the activated Mo-Mn method and active metal brazing method have developed into common industrial technologies, which are used for sealing high-temperature resistant ceramics (such as alumina, zirconia, silicon nitride, etc.) and metals (such as stainless steel, copper, molybdenum, etc.). In comparison, the sealing strength of direct copper coating method and ion sputtering method is not high, and the scope of application is greatly limited.

[0004] As ceramic-based electronic components develop towards miniaturization and integration, as well as the complexity of ceramic components and the diversification of application scenarios, existing sealing materials and technologies face huge challenges. The activated Mo-Mn method and active metal brazing method are complex and costly, and the operating temperature usually needs to be as high as 1000 degrees Celsius or above. Therefore, they are not suitable for sealing ceramics with metals with low melting points (such as aluminum), nor for some functional devices that are not resistant to high temperatures, such as piezoelectric ceramics, lasers, display elements, etc. In addition, metal sealing materials have poor acid resistance and are easily oxidized in long-term high-temperature environments. They cannot be used in ceramic-based devices or components that serve at high temperatures, such as fuel cell stacks.

[0005] Low-melting-point glass is an inorganic sealing material with great application potential developed in recent years. It has the advantages of stable chemical properties, high mechanical strength, simple process and low cost. It can be used for interconnection or airtight packaging between ceramics, metals, semiconductors and other materials. Low-melting-point glass is superior to organic polymer materials in terms of air tightness and heat resistance, and superior to metal materials in terms of chemical stability and insulation. Through the design of glass network structure and element composition, the softening temperature or melting temperature of glass can be controlled in a wide range from nearly 400 degrees Celsius to more than 1000 degrees Celsius, which can meet the needs of different sealing temperatures.

[0006] According to the composition system of glass network formers, low melting point glasses include silicates, borates, borosilicates, phosphates, tellurites, vanadates, etc. When used as sealing materials, these glasses have their own advantages and disadvantages. Among them, silicate glass forms a network structure through [SiO4] tetrahedron connections, with high mechanical strength and good chemical stability, but high operating temperature. Borate glass contains two structures, [BO3] triangles and [BO4] tetrahedrons, with a low softening temperature and good affinity with ceramic materials, but poor affinity with metals. Phosphate glass has good affinity with metals and a wide adjustable range of thermal expansion coefficients, but poor mechanical strength and chemical stability.

[0007] Therefore, in view of the technical characteristics of ceramic-metal sealing, it is necessary to organically integrate multiple systems of low-melting-point glasses and complement each other's advantages to achieve a significant improvement in sealing efficiency. Summary of the invention

[0008] The present invention provides a low melting point glass composed of three glass network formers: silicon oxide, boron oxide and phosphorus oxide.

[0009] The chemical composition of the low melting point glass of the present invention, calculated by molar percentage of oxides, comprises 5%~30% SiO2, 5%~30% B2O3, 5%~25% P2O3, 5%~30% Bi2O3, 3%~15% Al2O3, 1%~10% Na2O, 1%~15% MgO, 1%~15% ZnO and 0%~10% of one or more of CuO, CoO, NiO, K2O, Li2O, CaO, TiO2, ZrO2, Fe2O3 and Y2O3.

[0010] The glass phase transition temperature of the low melting point glass of the present invention is 400-700°C, the softening temperature is 500-900°C, the sealing temperature is 600-1000°C, and the expansion coefficient is 4.0-10.0×10 -6 / K, suitable for sealing ceramics such as alumina, aluminum nitride, zirconium oxide, silicon carbide, silicon nitride, barium titanate and other ceramics with metals such as iron, aluminum, copper, nickel, silver and alloy materials. It has the characteristics of lead-free and environmentally friendly, good sealing airtightness, high mechanical strength and good chemical stability.

[0011] The low melting point glass of the present invention is in powder form, and its characteristic D50 particle size is 0.1-10 microns.

[0012] The method for preparing the low melting point glass and powder of the present invention mainly comprises the following steps: (1) Weigh the raw materials according to the oxide composition ratio, mix them evenly, put them into a quartz crucible, place them in an electric furnace at 1000~1500℃, and melt them at a constant temperature for 60~180 minutes; (2) quickly pouring the glass melt into deionized water and obtaining glass slag through water quenching; (3) Use a ball mill to grind the glass slag into D 50 Glass powder with a particle size of 0.1~10 microns.

[0013] During use, the low-melting-point glass of the present invention is firstly ground and mixed with a certain proportion of organic carriers (including solvents, thickeners, surfactants, etc.) to form a paste slurry; then the glass slurry is evenly coated on the surface of ceramic and metal sealing parts by screen printing, scraping, dipping or spraying; then it is dried at a low temperature of 200-400°C; finally, the sealing is completed at a high temperature of 600-1000°C.

[0014] The thermal expansion coefficient of the low-melting point glass of the present invention is adjustable. When the difference in thermal expansion coefficients between the sealed ceramic and the metal is not too large, a single-component low-melting point glass with a thermal expansion coefficient between that of the ceramic and the metal can be used for sealing. When the difference in thermal expansion coefficients between the sealed ceramic and the metal is large, a two-component low-melting point glass with a higher and a lower thermal expansion coefficient can be used for sealing. During operation, a glass paste with a lower thermal expansion coefficient is applied to the surface of the ceramic, and a glass paste with a higher thermal expansion coefficient is applied to the surface of the metal, and then the ceramic and the metal are connected together and sintered. In this way, on the one hand, the problem of thermal expansion matching between the low-melting point glass and the sealed material can be solved; on the other hand, the two glass pastes fuse with each other during the sintering process to form a thermal expansion coefficient slow-changing layer, which can effectively disperse the internal stress of the seal.

[0015] Compared with the conventional activated Mo-Mn method or active metal brazing method, the low melting point glass of the present invention has the following beneficial effects: (1) The low-melting-point glass is an inorganic composite oxide material, which has good chemical stability and sealing tightness, strong anti-aging ability and high mechanical strength; (2) The low melting point glass has a low sealing temperature and can provide a wide operating temperature range of 600-1000°C for different sealed materials and sealing implementation scenarios; (3) The thermal expansion coefficient of the low melting point glass is between 4.0 and 12.0 × 10 -6 / K is adjustable and is suitable for sealing most ceramics and metal materials. DETAILED DESCRIPTION

[0016] In order to explain the technical means adopted by the present invention to achieve the predetermined invention purpose and to make the disclosure of the present invention more complete, the following is a detailed description in conjunction with embodiments. This embodiment helps those skilled in the art to which the present invention belongs to better understand the scope of the present invention, but the present invention is not limited to the embodiments disclosed below.

[0017] 1. Preparation of low melting point glass and powder

[0018] The chemical composition of the low melting point glass used in Examples 1-3 is shown in Table 1. The preparation of the low melting point glass and its powder includes the following steps: (1) Weigh the raw materials according to the oxides and their proportions listed in Table 1, and stir and mix them in a mixer for 20 minutes; (2) Place the mixed raw materials into a quartz crucible, place it in an electric furnace at 1200-1400°C, and melt it for 60-120 minutes; (3) quickly pouring the glass melt into deionized water for quenching to obtain glass slag; (4) The glass slag and agate balls of equal mass and 10 mm in diameter were placed in an agate jar and ground using a ball mill at 300 rpm for 30 minutes to obtain D 50 Glass coarse powder with a particle size of 20-30 microns; (5) By mass, 1 part of glass coarse powder, 3 parts of 3 mm agate balls, and 3 parts of deionized water were placed in an agate jar and ground using a ball mill at 400 rpm for 60-120 minutes to obtain D 50 Glass powder with a particle size of 1.0~2.0 microns; (6) The milled glass wet powder is dried at 120°C and finally passed through a 200-mesh sieve to obtain the finished product.

[0019] Table 1 Chemical composition (molar percentage) of the low melting point glass powders of Examples 1-3.

[0020]

[0021] 2. Low melting point glass and The glass phase transition temperature of the glass was measured using a differential scanning calorimeter; the softening temperature of the glass was measured using an image sintering instrument; the thermal expansion coefficient of the glass was measured using a fused quartz expansion analyzer; and the particle size and distribution of the glass powder was measured using a laser particle size analyzer.

[0022] Table 2 shows the glass transition temperature, softening temperature, thermal expansion coefficient and D50 particle size of the low melting point glass powder prepared in Examples 1 to 3.

[0023] Table 2 Basic physical properties of the low melting point glasses prepared in Examples 1 to 3.

[0024]

[0025] 3. Sealing application of low melting point glass 1. Glass paste preparation The low melting point glass powder prepared in Examples 1 to 3 was mixed with an organic phase carrier in a mass ratio of 6:4 and rolled into a glass paste using a three-roll mill. The organic carrier was a mixture of ethyl cellulose and pinene alcohol. The mass ratio of ethyl cellulose to pinene alcohol was 7:3. The viscosity of the glass paste prepared in Examples 1 to 3 was measured at 25°C and 50rpm using a constant temperature rotation viscometer and was 80±5 Pa·s.

[0026] 2. Sealing operation The low melting point glasses prepared in Examples 1 to 3 are respectively used for sealing an alumina ceramic sheet with an aluminum plate, a zirconia ceramic sheet with a stainless steel plate, and an aluminum nitride ceramic sheet with a copper plate. The sealing parameters are shown in Table 3. The operation steps are as follows: (1) Use acetone and deionized water to clean the surface of the sealing material, and blow dry with nitrogen; (2) A layer of glass paste with an area of ​​1.0 cm×1.0 cm is applied on the surface of the sealing material by screen printing. Example 1 uses two-component glass, wherein glass #1 paste is applied on the surface of the alumina ceramic sheet, and glass #2 paste is applied on the surface of the metal aluminum plate. Example 2 only uses single-component glass #3 paste. Example 3 uses two-component glass, wherein glass #4 paste is applied on the surface of the aluminum nitride ceramic sheet, and glass #5 paste is applied on the surface of the metal copper plate; (3) After the ceramic and metal are connected, o Dry in air atmosphere for 60 minutes; (4) Sealing was performed using a nitrogen atmosphere electric furnace. The sealing temperatures of Examples 1-3 were 600 o C. 780 o C and 850 o C, constant temperature treatment time is 30 minutes.

[0027] Table 3 Sealing parameters of Examples 1 to 3.

[0028]

[0029] 3. Sealing performance Table 4 shows the sealing performance evaluation results of Examples 1 to 3. The sealing strength of the seals was measured using a tensile strength tester; the seals were tested by 72 hours of double 85 (85% humidity, 85 o C) Test and evaluate the reliability of the seal; evaluate the acid corrosion resistance of the seal by testing the seal strength after immersion in 0.5% sulfuric acid solution for 0.5 hours; observe the density of the seal cross section with the help of a scanning electron microscope.

[0030] Table 4 Evaluation results of sealing performance of low melting point glasses prepared in Examples 1 to 3.

[0031]

[0032] As shown in Table 4, the sealing strength of the low-melting-point glass prepared in Examples 1 to 3 is greater than 7MPa. After 72 hours of double 85 test and 0.5 hours of immersion in 0.5% sulfuric acid solution, the sealing strength of Examples 1 to 3 decreased to varying degrees, but all were greater than 3.5MPa, indicating that the prepared low-melting-point glass has high sealing reliability and acid corrosion resistance. By observing the sealing section through a scanning electron microscope, the porosity of the sealing glass layer of Examples 1 to 3 is less than 0.1%, indicating good airtightness.

[0033] Finally, it should be noted that the specific technical features described in Examples 1-3 can be combined in a suitable manner without contradiction. Any simple modification or equivalent changes made to the above embodiments are within the scope of the technical solution of the present invention.

Claims

1. A low melting point glass for ceramic and metal sealing, characterized in that: The low melting point glass comprises three glass network formers of silicon oxide, boron oxide and phosphorus oxide, and comprises 5% to 30% SiO2, 5% to 30% B2O3 and 5% to 25% P2O3 in terms of oxide molar percentage.

2. The low melting point glass according to claim 1, characterized in that: The network intermediates and network ligands of the low-melting point glass, calculated by molar percentage of oxides, comprise 5%~30% Bi2O3, 3%~15% Al2O3, 1%~10% Na2O, 1%~15% MgO, 1%~15% ZnO and 0%~10% of one or more of CuO, CoO, NiO, K2O, Li2O, CaO, TiO2, ZrO2, Fe2O3 and Y2O3.

3. The low melting point glass according to claim 1 or 2, characterized in that: The low melting point glass is in powder form, and its characteristic D50 particle size is 0.1-10 microns.

4. The low melting point glass according to claim 1, 2, or 3, characterized in that: The low melting point glass is used for sealing ceramics such as alumina, aluminum nitride, zirconium oxide, silicon carbide, silicon nitride, barium titanate, etc. and metals such as iron, aluminum, copper, nickel, silver, etc. and alloy materials.

5. The low melting point glass according to claim 4, characterized in that: The low melting point glass slurry can be coated on the surface of ceramic and metal materials by adopting processes such as screen printing, scraping, dipping or spraying.

6. The low melting point glass according to claim 5, characterized in that: The low melting point glass can provide matching of higher and lower thermal expansion coefficients. During implementation, the glass paste with lower thermal expansion coefficient is coated on the ceramic surface, while the glass paste with higher thermal expansion coefficient is coated on the metal surface.

Citation Information

Patent Citations

  • Leadless barium borate low melting glass and application thereof

    CN101164939A

  • Sealing glass powder with high expansion coefficient as well as preparation method and application thereof

    CN116119933A

  • Leadless phosphate seal glass and its preparation method

    CN1830856A

  • Glass powder, composite powder, and low expansion substrate with decorative layer

    WO2016084627A1